2015
DOI: 10.5935/0101-2800.20150033
|View full text |Cite
|
Sign up to set email alerts
|

Different induction therapies for kidney transplantation with living donor

Abstract: The use of induction therapy resulted in lower rates of rejection in transplantation with living donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…In the multivariate analysis, the variable associated with a better renal outcome was induction therapy (basiliximab or thymoglobulin use), as previously demonstrated in this study, 20 and similar results were found by de Castro et al 21 …”
Section: Discussionsupporting
confidence: 88%
“…In the multivariate analysis, the variable associated with a better renal outcome was induction therapy (basiliximab or thymoglobulin use), as previously demonstrated in this study, 20 and similar results were found by de Castro et al 21 …”
Section: Discussionsupporting
confidence: 88%
“…A similar finding was reported by Nga et al in a retrospective cohort study on 90 LDKTR. Based on that study, creatinine levels at discharge and 6 months after discharge were 1.22±0.4 and 1.33±0.5 mg/dL in the thy-moglobulin group, 1.28±0.5 and 1.34±0.7 mg/dL in patients who were prescribed basiliximab, and 1.59±0.7 and 1.36±0.5 mg/dL in patients not receiving induction therapy, with no significant difference between the study groups (12).…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies showed that Antithymocyte globulin was more effective in the prevention of acute rejection when compared to basiliximab. 13,15 Except the Mexican study in deceased donors. 17 In our study acute rejections between the two arms were comparable (ATG 15.2% Vs. Basiliximab 16.9%, P=0.867).…”
Section: Image 1 Discussionmentioning
confidence: 99%